New Ways to Approach Pain Management in the ED - Rizzo, Toni (MD Conference Express, 2014)
Pain is the number one patient complaint in the emergency department (ED). This article reviews current recommendations for alleviating patient pain in the ED and improving patients’ overall satisfaction. He specifically addressed the pros and cons of low-dose ketamine, nerve blocks, and patient-controlled analgesia.